Minority, Cultural Citizenship, and Indonesian Islam: Challenges in a Pluralistic Society - Qodir, Zuly; Hefner, Robert W (Indonesian Journal of Islam and Muslim Societies, 2025)
Minority citizenship is a very important dimension that gets attention in a pluralistic country like Indonesia. This is because minority citizens often receive discriminatory, intimidating, and violent treatment from members of the majority religious, ethnic and social groups. Cultural citizenship related to religion, ethnicity and social groups is thus a development study of purely political citizenship studies. Three main findings were obtained through the research. First, multicultural citizenship is a very authentic idea that minority groups aspire to; second, the actions that promote and hinder the recognition of multicultural citizenship in social interactions; and third, the concerns that minority groups in Yogyakarta, and even Indonesia in general, have and experience. This article is intended to contribute to the understanding of multicultural citizenship within the social political life of post reform Indonesia amidst the phenomenon of rampant Islamization. Theoretically speaking, the article aims to contribute to developing a more authentic and strategic citizenship perspective so that the recognition of minority groups in a Muslim-majority country can transpire harmoniously, not confrontationally.